QUESTIONING STRATEGIES AND STUDENTS’ PREFERENCES: : BETWEEN REALITY AND EXPECTATION - Ninuk Krismanti; Fahmi Hidayat (Universitas Putera Batam, 2021)
This study was set to investigate questioning strategies employed by lecturers and students’ preferences on the strategies. The study involved two lecturers of general English classes of two different institutions and 80 students. The data were collected using observation and questionnaire. The researchers conducted the observations four times online to get the data on lecturers’ questioning strategies. The observed classes were recorded to help the analysis. Questionnaire was distributed to all students to get the data on students’ preferences regarding questioning strategies, but only 72 students responded the questionnaire. The findings of this study showed that probing and redirecting strategy were most frequently employed by the lecturers. Repeating was the strategy employed the least. On students’ side, most students chose prompting as their favorite. Students also agreed that types of questions also matter in determining their responses to the questions.